Current controversies: Null hypothesis significance testing - Philip M. Sedgwick; Anne Hammer; Ulrik Schiøler Kesmodel; Lars Henning Pedersen (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Traditional null hypothesis significance testing (NHST) incorporating the critical level of significance of 0.05 has become the cornerstone of decision‐making in health care, and nowhere less so than in obstetric and gynecological research. However, such practice is controversial. In particular, it was never intended for clinical significance to be inferred from statistical significance. The inference of clinical importance based on statistical significance (p < 0.05), and lack of clinical significance otherwise (p ≥ 0.05) represents misunderstanding of the original purpose of NHST. Furthermore, the limitations of NHST—sensitivity to sample size, plus type I and II errors—are frequently ignored. Therefore, decision‐making based on NHST has the potential for recurrent false claims about the effectiveness of interventions or importance of exposure to risk factors, or dismissal of important ones. This commentary presents the history behind NHST along with the limitations that modern‐day NHST presents, and suggests that a statistics reform regarding NHST be considered.